Legal Proof of Cybercrime: A Case Study of the Hacking of Bank Syariah Indonesia (BSI) - Ramdhan Mahardika Nasyith; Marchello Putra Toding Palilli; Triswer Triswer; Russell Dante Wiranatakusumah; Telly Augustine (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This research aims to analyze legal evidence for cybercrime through a case study of the hacking of Bank Syariah Indonesia (BSI). The method used is normative legal research with a statutory, case, and conceptual approach. The results show that evidence in cybercrime relies heavily on digital evidence such as system logs, electronic data, and malware analyzed through digital forensics. The validity of electronic evidence has been recognized in Article 5 paragraph (1) and Article 44 of the Electronic Information and Transactions Law (UU ITE), and is supported by Article 235 paragraph (1) of the new Criminal Procedure Code (KUHAP). However, the evidentiary process faces various obstacles such as the anonymity of the perpetrator, the cross-border nature, and the vulnerability of digital evidence to manipulation. Therefore, it is necessary to increase the capacity of law enforcement officers, strengthen cybersecurity systems, and collaborate across institutions and internationally to support effective law enforcement against cybercrime.